EFFECT OF RAMI FIBER IMMERSION DURATION ON TURI LEAF EXTRACT AS A PRESERVATIVE FOR FISH CATCHING - Nurhanifah Nurhanifah; Nofrizal Nofrizal; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe aim of this research is to find out how long the immersion effect of flax fiber on turi leaf extract is to determine the value of breaking strength and elongation of the fiber. The method used in this study is an experimental method that is by experimenting the length of time soaking hemp fiber in turi leaf extract as a fishing gear with soaking time for 0 weeks to 12 weeks. The value of breaking strength and elongation of the fibers were tested using Breaking Strength Tester. Data analysis using complete random design. The value of breaking strength of flax fiber that has been soaked has increased every week and the highest peak in the 9th week is 2.8 kgf / mm2 but in the 10th week through the 12th week has decreased. The value of flax fibers has increased unstable. The highest peak of elongation is at week 1 is 28.55 mm and the lowest stretch of flax fiber is at week nine which is 22.65mm. The results show that turi leaf extract is able to increase the breaking strength and elongation of flax fiber.Keywords: breaking strength, elongation, flax fiber,turi leaf extract